Tingkat Pengetahuan Petani Tentang Pestisida pada Tanaman Padi di Desa Kasarangan Kecamatan Labuan Amas Utara Kabupaten Hulu Sungai Tengah - Susi Wahyudi; Taufik Hidayat; Nurmelati Septiana (AGRIDES: Jurnal Agribisnis Perdesaan, 2015)
Recently various types and brands of pesticide have circulated on the area of Hulu Sungai Tengah. Each of product s has label and packaging,which show the advantages as well as certification of safety. Mast of them have been used by farmers, especially paddy grower. The study excavates the level of farmer knowledge on pesticide use, and identifies internal and external factors which affect farmers ' knowledge in Desa Kasarangan, Kecamatan Labuan Amas Utara, Kabupaten Hu/u Sungai Tengah. The farmers have high knowledge of pesticide use (score 87.87%}. The internal factors do not have a significant correl ation to level of knowledge, while the external factor (land acreage) has significant corre lation.